Effects of Gamma Irradiation on Agromorphological Characteristics of Okra (Abelmoschus esculentus L. Moench.). (3rd August 2017) - Asare, Aaron Tettey; Mensah, Francis; Acheampong, Samuel; Asare-Bediako, Elvis; Armah, Jonathan
Abstract : Cultivation of okra in Ghana is challenged by low yield due to lack of improved varieties. Gamma irradiated okra seeds can generate genetic variability to improve the crop. Samples of 150 seeds, each of okra genotype, UCCC6, were irradiated with 400 Gy to 1000 Gy using cobalt 60 source at a dose rate exposure of 121.58 Gy/hr. There were 40 stands comprising single plant per stand in three replications per treatment in a randomized complete block design outlay. Seedling survival, plant height, number of leaves, stem diameter, number of branches, leaf length and width, days to 50% flowering, number of fruits, length and weight of fruit, number of seeds, and 100-seed weight decreased significantly (P ≤ 0.05 ) with increasing doses of gamma rays. Seedling survival was highest (88%) at 400 Gy, followed by control (81%). However, 600 Gy, 800 Gy, and 1000 Gy had 61%, 41%, and 17% seedling survival, respectively, with LD50 at 720 Gy. Significant (P ≤ 0.05 ) correlations existed between growth and yield components. Optimum growth and yield in okra were induced by 400 Gy but the higher doses had growth retardation effects and the induced variability can be assessed at M2 generation.